Propriedades mecânicas e térmicas de compósitos de poliestireno e MDF - Kreutz, Juliana Cristina (2019)
The objective of this study was to evaluate the polystyrene composites with the incorporation of residue of medium density fiberboard (MDF), aiming application in engineering materials. It was developed virgin polystyrene (PS) composites reinforced with MDF residue, considering the influence of the fiber content, using the contents of 0, 2, 4, 6 and 8% by mass of the residue. The composites were obtained by means of a manual homogenization, followed by extrusion in monorrosca and injection molding. The composites were evaluated for their morphology by scanning electron microscopy (SEM). The functional groups were identified by Fourier transform infrared spectroscopy (FTIR) and the thermal behavior was analysed by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Mechanical tests and degradation study under ultraviolet (UV) radiation were also carried out. The results demonstrated that the best properties were obtained for the composite with 2% by mass of MDF residue. It has been found that the addition of the residue enhances the thermal stability of the polystyrene when compared to its pure form, which corroborates the idea of incorporating that residue into the polymer, considering that the same which is inappropriately discarded in the nature. The composites morphology showed homogeneity, as well as few voids after the material fracture. In the tests of degradation under UV radiation it was verified that the presence of the fiber did not prevent the degradation of the material, however, it was observed that the presence of the MDF residue delays the degradation process of the matrix, when evaluated by means tensile strength. It was concluded that the use of the MDF residue is feasible in obtaining polymeric composites, reducing the amount of the same that are inadequately descarted. Composites of polystyrene reinforced with MDF residue have good properties and can be used as materials for engineering applications.